Metal (II) Complexes of some Carboxylic group Drugs: Chelation, Characterization, Antibacterial, Analgesic, and Toxicology Studies: Biological Potentials of Carboxylic Group Drug Complexes - P. Ejidike, Ikechukwu; O. Bamigboye, Mercy; B. Njoku, Chima; Lawal, Misitura (Iranian Journal of Pharmaceutical Sciences, 2021)
The present work focuses on the synthesis and biological evaluation of metal complexes of mixed acetylsalicylic acid and para-aminobenzoic acid in ratio 1:1:1 to give a complex type: [M(ASA)(PABA)(H2O)n(Cl2)x](Cl2)y (where M = Cu(II), Cd(II), Ni(II), Fe(III), or Mn(II); ASA = Acetylsalicylic acid; PABA = para-aminobenzoic acid; n = 0 or 2; x = 0 or 1; y = 0 or 1). The metal complexes were obtained by a refluxing method and characterized by elemental analysis, melting point, conductivity measurements, ultraviolet-visible absorption, and infrared spectroscopy. The conductance measurement indicates the non-electrolytic nature of the complexes. The octahedral environment has been proposed for the complexes except for Cd (II) complex. The level of toxicity of the synthesized complexes was determined in vivo. [Cu(ASA)(PABA)(H2O)2], [Cd(ASA)(PABA)]Cl2, and [Mn(ASA)(PABA)(H2O)2] exhibited higher enzymatic activities in the serum and kidney homogenates of the Wister rats investigated. The acetic acid-induced writhing model method was used in the evaluation of the analgesic activities of the prepared complexes. Metal complexes of Cu (II), Cd(II), Ni(II), Fe(III), and Mn(II) exhibited percentage writhing inhibition of 67.61, 43.87, 60.42, 70.45, and 52.34 % respectively. The complexes proved to be more effective than their parent-free ligands with Fe (III) possessing the highest analgesic potentials. The in vitro antimicrobial activity against bacterial strains was studied using the agar well diffusion procedure. It was also observed that the complexes exhibited higher bacteriostatic activities than the free ligands.